1896
DOI: 10.1002/cber.18960290190
|View full text |Cite
|
Sign up to set email alerts
|

Ueber Thianthren und Selenanthren, C12H8Se2. II

Abstract: Thianthren und SeIenanthren, C1gHs Se2. 11. (Eingegangen am 26. Februar.) Zur Darstellung des Selenanthrens erhitzt man in einem zur Vacuumdestillation geeigneten Kijlbchen rnit angeschmolzener Vorlage j e 10 g Thianthrendisulfon, die man zuvor mit 5.7 g Selen sorgfaltig

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…23 Previous reports included neither 4 or selenanthrene-5,5,10,10-tetroxide (5) (both containing a selenone moiety). 1,21,22 However, we found that 4 did form after treating 1 with 4 equiv of m-CPBA and heating for 48 h. We made a minor attempt to obtain 5 by reaction of 1 with 10 equiv of m-CPBA in refluxing 1,2dichloroethane for 72 h. The major product from this reaction remained as 4; however, a very downfield 1 H NMR resonance was observed at 8.84 ppm, which we attribute to the presence of 5; we postulate that 5 could be obtained more cleanly if a stronger oxidant was used. One such reagent is dioxirane; it is more nucleophilic than m-CPBA and thus would more easily oxidize the electrophilic selenoxide in 4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…23 Previous reports included neither 4 or selenanthrene-5,5,10,10-tetroxide (5) (both containing a selenone moiety). 1,21,22 However, we found that 4 did form after treating 1 with 4 equiv of m-CPBA and heating for 48 h. We made a minor attempt to obtain 5 by reaction of 1 with 10 equiv of m-CPBA in refluxing 1,2dichloroethane for 72 h. The major product from this reaction remained as 4; however, a very downfield 1 H NMR resonance was observed at 8.84 ppm, which we attribute to the presence of 5; we postulate that 5 could be obtained more cleanly if a stronger oxidant was used. One such reagent is dioxirane; it is more nucleophilic than m-CPBA and thus would more easily oxidize the electrophilic selenoxide in 4.…”
Section: Resultsmentioning
confidence: 99%
“…All other inorganic reagents were purchased from Fisher Scientific and used as received. 1 H, 13 C (101 MHz) and 77 Se NMR (76 MHz) spectra were collected on a Varian DirecDrive instrument equipped with a 400 MHz OneNMR 5 mm probe. Variable temperature NMR spectra were collected on a Varian Oxford 600 MHz instrument equipped with a 600 MHz OneNMR 5 mm probe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations